Site‐Selective Acylation of Pyranosides with Immobilized Oligopeptide Catalysts in Flow. Issue 18 (22nd February 2023) - Seitz, Alexander; Wende, Raffael C.; Schreiner, Peter R.
Abstract: We report the site‐selective acetylation of partially protected monosaccharides using immobilized oligopeptide catalysts, which are readily accessible via solid‐phase peptide synthesis. The catalysts are able to invert the intrinsic selectivity, which was determined using N ‐methylimidazole, for a variety of pyranosides. We demonstrate that the catalysts are stable for multiple reaction cycles and can be easily reused after separation from the reaction solution. The catalysts can also be used in flow without loss of reactivity and selectivity. Abstract : We describe the immobilization of oligopeptide catalysts and their use in the site‐selective acetylation of different monosaccharides. The catalysts are easy to synthesize, can easily be reused for several reactions, and are able to perform well in first continuous flow experiments.